2007
DOI: 10.1152/ajpheart.00219.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species contribute to sleep apnea-induced hypertension in rats

Abstract: In clinical studies, sleep apnea is associated with hypertension, oxidative stress, and increased circulating endothelin-1 (ET-1). We previously developed a model of sleep apnea by exposing rats to eucapnic intermittent hypoxia (IH-C) during sleep, which increases both blood pressure and plasma levels of ET-1. Because similar protocols in mice increase tissue and plasma markers of oxidative stress, we hypothesized that IH-C generation of reactive oxygen species (ROS) contributes to the development of ET-1-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 46 publications
9
67
2
Order By: Relevance
“…Numerous lines of evidence indicate that oxidative stress affects the vascular tone, on one hand through decreased NO bioavailability contributing to endothelial dysfunction and, on the other hand, by promoting vascular cell proliferation, inflammation, and extracellular matrix remodeling 8. Our results are in accordance with previous studies demonstrating that long‐term exposure to IH induces vascular oxidative stress13, 14 (ie, superoxide anion production) and inflammation10, 11, 12, 44, 46 (ie, NF‐κB, F4/80, CD45, and interferon‐γ expression). In addition, using in vitro transendothelial electrical resistance measurement, we demonstrated that IH also induces endothelial barrier dysfunctions, confirming recent data from Prabhakar's group that demonstrates in endothelial cell cultures a central role of reactive oxygen species in promoting IH‐associated endothelial barrier dysfunctions 47.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Numerous lines of evidence indicate that oxidative stress affects the vascular tone, on one hand through decreased NO bioavailability contributing to endothelial dysfunction and, on the other hand, by promoting vascular cell proliferation, inflammation, and extracellular matrix remodeling 8. Our results are in accordance with previous studies demonstrating that long‐term exposure to IH induces vascular oxidative stress13, 14 (ie, superoxide anion production) and inflammation10, 11, 12, 44, 46 (ie, NF‐κB, F4/80, CD45, and interferon‐γ expression). In addition, using in vitro transendothelial electrical resistance measurement, we demonstrated that IH also induces endothelial barrier dysfunctions, confirming recent data from Prabhakar's group that demonstrates in endothelial cell cultures a central role of reactive oxygen species in promoting IH‐associated endothelial barrier dysfunctions 47.…”
Section: Discussionsupporting
confidence: 92%
“…In OSA, it has been shown that venous endothelial cells from apneic patients exhibited local oxidative stress and inflammation associated with decreased NO bioavailability and reduced flow‐mediated dilation 9. Experimental studies in rodents demonstrated that chronic IH per se represents a causal factor of vascular remodeling and hypertension,10, 11, 12, 13, 14 in part through vascular inflammation10, 11, 12 and oxidative stress 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…Increased plasmatic levels of ROS and ET-1 have been also implicated in the hypertension induced by intermittent hypoxia. Troncoso-Brindeiro et al, (2007) reported that the concurrent treatments of rats exposed to intermittent hypoxia with the SOD mimetic, 4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPOL), prevents the increased ROS plasmatic level and the hypertension. However, it is worth noting that intermittent hypoxia increases the expression of ET-1 in the rat CB during the first week of hypoxia, and later the ET-1 levels returned back to the control levels (Del Rio et al, 2011), suggesting that ET-1 may contribute to the enhanced carotid body responsiveness to hypoxia in the early phase of the intermittent hypoxic exposures.…”
Section: Vasoactive Moleculesmentioning
confidence: 99%
“…The latter approach is proposed for the study of the hypoxic consequences of sleep apnea, and such various short-cycle hypoxia reoxygenation paradigms are accompanied by metabolic effects on lipid metabolism [17] and glucose intolerance [18]. These effects are in part secondary to the development of free oxygen radicals formed in the hypoxia reoxygenation process [19]. The common approach to model the hypoxia of chronic lung disease is a 23 -24 hour exposure to hypoxia for 2 -3 weeks.…”
Section: Discussionmentioning
confidence: 99%